A case-report of successful photodynamic therapy of the patient with severe vulvar dysplasia - E. V. Filonenko; L. G. Serova (Biomedical Photonics)
A case of successful photodynamic therapy (PDT) of the patient with grade 3 vulvar dysplasia. One course of treatment with photolon was performed. The photosensitizer was administered intravenously as 30 min infusion in dose of 1.0 mg/kg body weight. The PDT session was performed 3h after infusion of photolon, the light dose was 350 J/cm2. The treatment was well tolerated. Due to PDT a complete tumor regression was achieved. The patient received a strict follow-up schedule, for 8 months after PDT no recurrence was observed.